Therapeutic effects of fatty acid binding protein 1 in mice with pulmonary fibrosis by regulating alveolar epithelial regeneration - Ying He; Shuang Li; Qun Luo; Jin Su; Xiaomin Peng; Zhenli Fu; Hang Yin; Jiani Liu; Shengren Song; Xihui Huang; Yunxin Lai; Penghui Yang (BMJ Open Respiratory Research)
Introduction Idiopathic pulmonary fibrosis is a progressive fibrotic lung disease with limited therapeutic options and high lethality, related to alveolar type II epithelial (ATII) cell dysregulation, the abnormal repair of alveolar epithelial cells and activation of fibroblasts promote the development of pulmonary fibrosis. Fatty acid binding protein 1 (FABP1) was significantly downregulated in the fibrotic state by proteomics screening in our previous date, and the ATII cell dysregulation can be mediated by FABP1 via regulating fatty acid metabolism and intracellular transport. The aim of this study was to evaluate the role and potential mechanism of FABP1 in the development of pulmonary fibrosis.Methods Proteomics screening was used to detect changes of the protein profiles in two different types (induced by bleomycin and silica, respectively) of pulmonary fibrosis models. The localisation of FABP1 in mouse lung was detected by Immunofluorescence and immunohistochemistry. Experimental methods such as lung pathology, micro-CT, western blotting, small animal imaging in vivo, EdU, etc were used to verify the role of FABP1 in pulmonary fibrosis.Results The expression of FABP1 in the mouse lung was significantly reduced in the model of pulmonary fibrosis from our proteomic analysis and immunological methods, the double immunofluorescence staining showed that FABP1 was mainly localised in type II alveolar epithelial cells. Additionally, the expression of FABP1 was negatively correlated with the progression of pulmonary fibrosis. Further in vivo and in vitro experiments showed that overexpression of FABP1 alleviated pulmonary fibrosis by protecting alveolar epithelium from injury and promoting cell survival.Conclusion Our findings provide a proof-of-principle that FABP1 may represent an effective treatment for pulmonary fibrosis by regulating alveolar epithelial regeneration, which may be associated with the fatty acid metabolism in ATII cells.